The Slack Factor: Resources Influencing Carbon Transparency - Rahman, Md Arafat; Abdullah, Samiha Binte; Islam, Mohaimenul; Hasan, Riaz; Nur, Farlin (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of slack resources—financial slack, human resource slack, and R&D intensity—on carbon emission disclosure (CDI) among top-listed firms in Bangladesh and India. It explores how both local and global resource availability influences carbon-related disclosure practices in emerging markets. Using data from 150 firms over the period 2019-2021, the study employs descriptive analysis, correlation, and ordinary least squares (OLS) regression models to assess these relationships. A content analysis approach was adopted, utilizing a non-weighted (binary) index to evaluate corporate sustainability and annual reports. The findings reveal a significant positive association between R&D intensity and CDI, suggesting that firms investing in R&D are more likely to disclose carbon emissions. Conversely, financial and HR slack exhibit a negative relationship with CDI, indicating that firms with surplus resources may prioritize other strategic objectives over carbon disclosure. These results highlight the critical role of strategic resource allocation in shaping environmental disclosure, particularly in regulatory environments with weaker enforcement. By contributing to the limited literature on slack resources and environmental transparency in emerging economies, this study provides valuable insights for policymakers and businesses. It underscores the need for stronger regulatory frameworks and incentives to encourage firms to integrate sustainability into their corporate strategies.